Utilization of red rice (Oryza sativa) flour as partial substitute to all-purpose flour in cracker production. - Amante, Angel Hope B. (2018.)
Red rice which derives its red color from anthocyanins, has been popular and available over the last few years being a nutritious rice variety. Red rice is known to deliver protective antioxidant properties and anti-carcinogenic activities due to the presence of anthocyanins. This study intended to utilize red rice in the production of crackers. There were three cracker formulations developed: F1 containing 10% red rice flour and 90% all-purpose flour; F2 containing 20% red rice flour and 80% all-purpose flour; F3 containing 30% red rice flour and 70% all-purpose flour. F3 was most preferred by the sensory panel and perceived to have dark brown color, slightly perceptible red rice aroma, slightly perceptible red rice flavor, and slightly rough mouthfeel. Thirty-six percent (36%) of the seventy-five (75) consumer-respondents rated the product "like very much". the most preferred formulation (MPF) of red rice cracker had 2.18% moisture content, 14.77% crude fat, 0.14% crude fiber, 0.92% crude protein, 7.60% ash, 74.50% carbohydrates, 0.23 water activity, 4.94 pH, 3.75 N hardness, 434.5 kcal/g caloric value and 0.1651 mg/100g anthocyanin content. Except for the anthocyanin content, all parameters tested were statistically compared with that of the control. Red rice flour significantly increased fat, crude fiber, ash, and pH content and calorie content of crackers but significantly decreased the moisture and carbohydrate content. There was no significant difference on the protein content, hardness value and water activity of red rice cracker and the control.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Red rice; Red rice -- Crackers; Oryza sativa; Anthocyanins